Hypertrophic Olivary Degeneration: A Neurosurgical Point of View - Carvalho, Carlos Henrique; Kimmig, Hubert; Lopez, William Omar Contreras; lange, Manfred; Oeckler, Reinhard (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2016)
Hypertrophic olivary degeneration (HOD) is a rare form of transsynaptic degeneration characterized by hypertrophy of the inferior olivary nucleus situated in the olivary body, part of the medulla oblongata, representing a major source of input to the cerebellum. HOD typically results from focal lesions interrupting connections from the inferior olive within the dentato-rubro-olivary pathway, a region also known as the triangle of Guillain-Mollaret (TGM) (red nucleus, inferior olivary nucleus, and contralateral dentate nucleus). Clinically, HOD presents classically as palatal tremor and can include dentatorubral tremor and/or ocular myoclonus. The pathologic changes associated with HOD feature radiologic changes with the inferior olivary nucleus appearing larger and increasing its T2-weighted signal intensity on magnetic resonance images. HOD is commonly managed with pharmacotherapy but may require surgical intervention in extreme cases. HOD has been found to develop as a consequence of any injury that disrupts the TGM pathways (e.g., pontine cavernoma).These findings highlight the critical importance of a thorough knowledge of TGM anatomy to avoid secondary HOD. We present a patient who developed HOD secondary to resection of a tectal plate cavernous malformation and review the literature with an emphasis on the current knowledge of this disorder.
Keywords: hypertrophic olivary degeneration (HOD); triangle of Guillain-Mollaret (TGM); symptomatic tremor; neurosurgical intervention